Field study 4 : exploring the curriculum - Salana, June P. (Manila, Philippines : Rex Book Store, 2010)
Field Study 4 - Exploring the Curriculum will allow the student to elaborate how theories of various teaching techniques in a subject area can contribute in a more positive manner to the development of quality learning experiences for the students in curriculum development. In these activities, students will analyze the learning needs and goals, and match the subject matter to the instructional methods. they may analyze the delivery system, include instructional materials and activities, and try and evaluate all instructions and learner activities.
Student's Expected Outcomes 1 -- Introduction 2 -- Field Studies 3 -- Curriculum Development 3 -- Metacognitive Strategies 24 -- Helpful Vocabulary - Pedagogy Guidelines 66 -- References 82.
Includes bibliographical references.
Keywords: CURRICULUM PLANNING